2016
DOI: 10.1080/15287394.2016.1211045
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary exposure to cellulose nanocrystals caused deleterious effects to reproductive system in male mice

Abstract: Over the past several years there has been an increased number of applications of cellulosic materials in many sectors, including the food industry, cosmetics, and pharmaceuticals. However, to date, there are few studies investigating the potential adverse effects of cellulose nanocrystals (CNC). The objective of this study was to determine long-term outcomes on the male reproductive system of mice upon repeated pharyngeal aspiration exposure to CNC. To achieve this, cauda epididymal sperm samples were analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 64 publications
(78 reference statements)
2
29
1
Order By: Relevance
“…While currently there are no published data revealing a safety concern for nanocellulose in the workplace or in consumer products, experimental evidence has been collected for the potential hazardous effects of CNCs and CNFs . While most cellular studies have addressed cytotoxicity, inflammation and genotoxicity, which can be related to differences in the cellular uptake of CNCs versus CNFs or their ability to generate oxidative stress, most in vivo studies have focused on the effects in the lung and the reproductive system . For instance, pulmonary exposure to CNCs is capable of generating dose‐dependent pro‐inflammatory effects and oxidative stress, while CNFs are capable of inducing TH1 polarizing effects in the lung .…”
Section: Discussionmentioning
confidence: 99%
“…While currently there are no published data revealing a safety concern for nanocellulose in the workplace or in consumer products, experimental evidence has been collected for the potential hazardous effects of CNCs and CNFs . While most cellular studies have addressed cytotoxicity, inflammation and genotoxicity, which can be related to differences in the cellular uptake of CNCs versus CNFs or their ability to generate oxidative stress, most in vivo studies have focused on the effects in the lung and the reproductive system . For instance, pulmonary exposure to CNCs is capable of generating dose‐dependent pro‐inflammatory effects and oxidative stress, while CNFs are capable of inducing TH1 polarizing effects in the lung .…”
Section: Discussionmentioning
confidence: 99%
“…Further evidence was shown that these biochemical effects led to significant genotoxicity [94]. In a further study, a similar author team elucidated further that the genotoxic effects were highly detrimental to the male reproductive system [95]. …”
Section: Introductionmentioning
confidence: 99%
“…However, to date, limited data are available describing adverse health outcomes elicited by CNCs. Therefore, the concept that CNCs are biocompatible and non‐hazardous, justified due to the fact that they are biobased, nanosized materials and can be extracted from natural sources, must be evaluated carefully and critically, since few studies have demonstrated that these materials might have toxic effects on cells …”
Section: Cytotoxicity Of Cncs: a Critical Evaluation Of The Biocompatmentioning
confidence: 99%